Seroinvestigation of Rubella virus of the oligozoospermia and azoospermia patients - Noor Kareem kadhim (Genius Journals, 2022)
The testis and epididymis are comparatively more relevant than accessory glands when it comes to inflammatory situations since they might become infected by microorganisms and become functionally compromised as a result
Keywords: Infertility; rubella virus; sperms; epididymitis